DISABILITY PROTECTION IN WORK-FAMILY BALANCE POLICIES IN THE GULF COOPERATION COUNCIL - Aref, Ahmed; Attia, Mostafa (PEOPLE: International Journal of Social Sciences, 2017)
Work–family balance (WFB) has come to the forefront of policy discourse globally in recent years. The emergence of both the Convention on the Rights of Persons with Disabilities (UNCRPD), along with Sustainable Development Goals (SDGs), has forced disability protection PEOPLE: International Journal of Social SciencesISSN 2454-5899Available Online at: http://grdspublishing.org/564to be a major policy concern as a cross cutting theme within the WFB frameworks. Disability protection has numerous variables and indicators through research and policy analysis. This paper highlights one important aspect of disability protection; which is how the WFB policies give priority to the employed parents of children with disabilities in the GCC. In order to address an existing research gap in this area, this policy-oriented paper will provide a critical overview of institutional and legislative mapping on the situation of disability protection from a WFB perspective in the GCC, ending up by suggesting policy recommendations towards better WFB provisions for employed parents of children with disabilities. The paper will depend on some document analysis to the current legislations that govern the rights of disabled people within GCC. The methodological framework will also include the MAP approach to present the current benefits given to parents who have disabled children.